2019
DOI: 10.1080/21505594.2019.1589364
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas of coxsackievirus-infected dams and their challenged pups: A complex issue

Abstract: Enteroviral infections are frequent, often asymptomatic in humans and during gravidity. The present study is an extension of our previous investigations where we had shown pancreatitis in challenged pups of CVB4-E2-infected dams. Present investigation describes the effect of gestational infection with this virus on the pancreas of both dams and their challenged pups. Gravid CD1 outbred mice were orally infected with CVB4-E2 virus at different gestation times. Pups were challenged orally with the same virus aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Also, our unpublished data show that the wild type strain of CVB2-Ohio does not induce any changes in the endocrine and exocrine pancreas but mild inflammation in the heart. Our studies (Bopegamage et al, 2012;Sarmirova et al, 2019) on the effect of gestational infection by CVB4-E2 on the pancreas of both dams and their challenged pups showed that the replicating virus was present in the pancreas of infected dams and their challenged pups. We also observed presence of inflammation leading to chronic necrotizing pancreatitis and atrophy of the acinar tissue of the dams and their offspring.…”
Section: Our Studies In the Murine Model Using The Oral Infectionmentioning
confidence: 69%
See 1 more Smart Citation
“…Also, our unpublished data show that the wild type strain of CVB2-Ohio does not induce any changes in the endocrine and exocrine pancreas but mild inflammation in the heart. Our studies (Bopegamage et al, 2012;Sarmirova et al, 2019) on the effect of gestational infection by CVB4-E2 on the pancreas of both dams and their challenged pups showed that the replicating virus was present in the pancreas of infected dams and their challenged pups. We also observed presence of inflammation leading to chronic necrotizing pancreatitis and atrophy of the acinar tissue of the dams and their offspring.…”
Section: Our Studies In the Murine Model Using The Oral Infectionmentioning
confidence: 69%
“…These studies show that it is important to know the background of the mice. The autoimmune aspects of coxsackievirus infection have been reviewed by Rose (2008).…”
Section: Viral Persistencementioning
confidence: 99%
“…Moreover, within the missed abortion group 5 cases were demonstrated to be CVB3-positive [ 3 ]. In a mouse model of CVB4-E2 infection during pregnancy, dams were infected at different time points during gravidity starting at embryonic day (E) 4 [ 58 ]. E4 is the time point of blastocyst implantation in the mouse [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human enteroviruses can be transmitted through oral routes, causing different illnesses, which can be serious. For example, coxsackievirus B (CVB) enterovirus, which can induce multi-organ disease, including pancreas and liver [17,[42][43][44][45], requires the use of appropriate in vitro models for its study. The use of conventional models does not allow us to reproduce the physical complexity of the human intestinal mucosa containing different cell types and properties, which include absorptive, mucus-secreting, enteroendocrine, Paneth cells and villus structures by using a static cell culture [46,47].…”
Section: Study Of Human Gastrointestinal Viral Infection Using Gut-on...mentioning
confidence: 99%